Quality Maintenance of Beef Burger Patties by Direct Addiction or Encapsulation of a Prickly Pear Fruit Extract - Parafati, Lucia; Palmeri, Rosa; Trippa, Daniela; Restuccia, Cristina; Fallico, Biagio (Frontiers in Microbiology, 2019)
Beef burger patties are a very perishable food with a maximum shelf life of 3 d at 4 °C, due to a fast decrease of quality parameters and microbial growth. Although some additives listed in the Commission Regulation (EC) No 601/2014 are allowed in fresh minced beef with antioxidant functionality, no additive with antimicrobial activity is permitted on fresh minced meat and meat preparations. Among natural preservatives, the prickly pear extract has attracted great scientific interest for its healthy properties, for the low cost of the raw material and for the high antibacterial activity when applied on fresh sliced beef and salami. In this study, a Prickly Pear Extract (PPE) was added to beef burger patty formulations both by direct application and encapsulation in alginate beads. Beef burger patties were evaluated during refrigerated storage (up to 8 d at 4 °C) in terms of microbial quality, pH, texture and color variation. At the end of storage, burger samples incorporating PPE and encapsulated PPE showed significantly (p<0.05) lower values of mesophilic bacteria, Enterobacteriaceae, and Pseudomonas spp. when compared to control samples added with sterile distilled water (SDW) or encapsulated SDW. Samples added with encapsulated PPE showed the smallest variations of color a* values (red) during the considered storage period, followed by sample added with PPE, suggesting a protective effect of the extract towards the myoglobine oxidation process. In addition, textural parameters (hardness, cohesiveness and springiness) reached the highest levels, after 8 d of storage, in burger samples added both with PPE and encapsulated PPE, supporting the potentiality of PPE, encapsulated or not into alginate beads, to be used as a natural additive of beef burger patty formulations for maintaining quality parameters and prolonging shelf life.